Grudge Spending: The Interplay between Markets and Culture in the Purchase of Security. Issue 4 (November 2015) - Loader, Ian; Goold, Benjamin; Thumala, Angélica
In the paper, we use data from an English study of security consumption, and recent work in the cultural sociology of markets, to illustrate the way in which moral and social commitments shape and often constrain decisions about how, or indeed whether, individuals and organizations enter markets for protection. Three main claims are proffered. We suggest, firstly, that the purchase of security commodities is a mundane, non-conspicuous mode of consumption that typically exists outside of the paraphernalia of consumer culture – a form of grudge spending. Secondly, we demonstrate that security consumption is weighed against other commitments that individuals and organizations have and is often kept in check by these competing considerations. We find, thirdly, that the prospect of consuming security prompts people to consider the relations that obtain between security objects and other things that they morally or aesthetically value, and to reflect on what the buying and selling of security signals about the condition and likely futures of their society. These points are illustrated using the examples of organizational consumption and gated communities. In respect of each case, we tease out the evaluative judgements that condition and constrain the purchase of security among organizations and individuals and argue that they open up some important but neglected questions to do with the moral economy of security.